(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored teachers' experiences relative to the school culture in the new normal. The researcher narrowed down the highlights and lowlights of their experiences, their effectiveness, and the teacher's coping practices on the challenges that come along the way. Specifically, this research aimed to answer the following questions about the teachers' experiences as they explored the culture in the new normal and the coping mechanisms for the challenges encountered. To achieve the objectives of the study, I made use of phenomenology. The 10 participants of this study are from Dr. Jovito S. Francisco Elementary School, Talomo A District, Davao City Division. I used a semi-structured online interview using the coding technique to analyze the data. The study, It was discovered the following themes from the participants these are; Adapting to new safety protocols and Navigating hybrid learning models Despite the negativity surrounding temporary or prolonged school closure, it positively impacted health and safety measures. blended learning offers one such opportunity to provide engaging learning opportunities to students by combining face-to-face medium of instruction with online learning opportunities. Other themes that emerge for the coping mechanisms are, Prioritizing Self-Care and Seeking Professional Development, of which It has been reported that immunity can limit the breakout and spread of infection While one has to remain hopeful, it must be noted that extreme caution needs to be undertaken to provide optimal learning.